TADRIB AL QIRA’AH AL JAHRIYAH BARNAMIJ AL MUSA’ID LADAY AT THALABAH - jannah, nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Student Problems Arabic Language Department Mohammedia University in Matamaram: Students can not appreciate the vocabulary skills. Students can not read well and do not understand what they have read. To acquire those skills, education needs to be taught in a way that is appropriate for students. Such as the program of reading aloud to help students.In this study, the researcher used the qualitative approach. The qualitative research is usually special in social science, which is essential to the observation of people in their environment, their treatment, their languages and their methods. The researcher starts from the data and may use the scientific theories for clarification.The results are: training in reading of the students of the Department of Arabic Language Education, Since the academic year 2014-2015. It has succeeded in helping students. This program was a